Q. 594.0( 1 Vote )

<span lang="EN-US

P(A) = 0.6 , P(B) = 0.2 , P = 0.5 (Given)

(1)

= 1 – 0.2

= 0.8

Also,

= 1 – P(AB) (3)

Using (2) & (3) in Equation (1) we get,

(3)

Now,

P(AB) = 0.5 P(B) From (Given)

P(AB) = 0.5 0.2

P(AB) = 0.1

According to the addition theorem of probability,

P(AB) = P(A) + P(B) – P(AB)

= 0.6 + 0.2 – 0.1

= 0.8 – 0.1

= 0.7 (4)

Putting (4) in equation (3) we get,

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

A bag contains 6 RD Sharma - Volume 2

A man is known toMathematics - Board Papers

A bag contaRD Sharma - Volume 2

Three persons A, Mathematics - Board Papers

Bag I contains 3 Mathematics - Board Papers

A speaks trRD Sharma - Volume 2

Two cards aRD Sharma - Volume 2

A bag contaRD Sharma - Volume 2

Kamal and MRD Sharma - Volume 2

Two balls aRD Sharma - Volume 2